Effects of human placenta cryopreservation on molecular characteristics of placental mesenchymal stromal cells - Navakauskienė, Rūta; Žukauskaitė, Deimantė; Borutinskaitė, Veronika Viktorija; Bukreieva, Tetiana; Skliutė, Giedrė; Valatkaitė, Elvina; Zentelytė, Aistė; Piešinienė, Lina; Shablii, Volodymyr (Frontiers in Bioengineering and Biotechnology, 2023)
Cryopreservation of placenta tissue for long-term storage provides the opportunity in the future to isolate mesenchymal stromal cells that could be used for cell therapy and regenerative medicine. Despite widely used established cryopreservation protocols, freeze and thawing still raise concerns about their impact on molecular characteristics, such as epigenetic regulation. In our study, we compared characteristics of human placental mesenchymal stromal cells (hPMSC) isolated from fresh (Native) and cryopreserved (Cryo) placenta tissue. We assessed and compared Native and Cryo hPMSC characteristics such as morphology, metabolic and differentiation potential, expression of cell surface markers and transcriptome. No significant changes in immunophenotype and differentiation capacity between Native and Cryo cells were observed. Furthermore, we investigated epigenetic changes and demonstrated that both Native and Cryo hPMSC express only slight variations in epigenetic profile, including miRNA levels, DNA methylation, and histone modifications. Nevertheless, the transcriptome analysis defined the upregulation of early-senescence state-associated genes in hPMSCs after cryopreservation. We also evaluated the ability of hPMSC to improve pregnancy outcomes in mouse models. Improved pregnancy outcomes in a mouse model confirmed that isolated placental cells both from Native and Cryo tissue have a positive effect on the restoration of reproductive system. Still the Native hPMSCs possess better capacity (up to 66 %) in comparison with Cryo hPMSC (up to 33%) to restore fertility in premature ovarian failure mice. Our study demonstrate that placental tissue can be cryopreserved for long-term storage with the possibility to isolate mesenchymal stromal cells that retain characteristics suitable for therapeutic potential.